Microperimetry in age-related macular degeneration: association with macular morphology assessed by optical coherence tomography. Issue 12 (1st February 2019) - Roh, Miin; Laíns, Inês; Shin, Hyun Joon; Park, Dong Ho; Mach, Steven; Vavvas, Demetrios G; Kim, Ivana K; Miller, Joan W; Husain, Deeba; Miller, John B
Abstract : Background/aims: Microperimetry is a technique that is increasingly used to assess visual function in age-related macular degeneration (AMD). In this study, we aimed to evaluate the relationship between retinal sensitivity measured with macular integrity assessment (MAIA) microperimetry and optical coherence tomography (OCT)-based macular morphology in AMD. Methods: Prospective, cross-sectional study. All participants were imaged with colour fundus photographs used for AMD staging (Age-Related Eye Disease Study scale), spectral-domain OCT (Spectralis, Heidelberg, Germany) and swept-source OCT (Topcon, Japan). Threshold retinal sensitivity of the central 10° diameter circle was assessed with the full-threshold, 37-point protocol of the MAIA microperimetry device (Centervue, Italy). Univariable and multivariable multilevel mixed-effect linear regression models were used for analysis. Results: We included 102 eyes with AMD and 46 control eyes. Multivariable analysis revealed that older age (p<0.0001), advanced AMD stage (p<0.0001) and reduced retinal thickness (p<0.0001) were associated with decreased mean retinal sensitivity. No associations were found between choroidal thickness and retinal sensitivity within the macula. Within the 10° diameter circle of the macula, the presence of ellipsoid disruption, subretinal fluid, atrophy and fibrosis, and outer retinal tubulation on OCT images was also associated with decreased retinal sensitivity (all p<0.05). Conclusions: There is an association between TRS as determined by MAIA microperimetry and several OCT structural parameters across various stages of AMD. This study highlights the relevance of microperimetry as a functional outcome measure for AMD.